The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1016/j.virol.2004.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Psittacid herpesviruses associated with mucosal papillomas in neotropical parrots

Abstract: Mucosal papillomas are relatively common lesions in several species of captive neotropical parrots. They cause considerable morbidity and in some cases, result in mortality. Previous efforts to identify papillomavirus DNA and proteins in these lesions have been largely unsuccessful. In contrast, increasing evidence suggests that mucosal papillomas may contain psittacid herpesviruses (PsHVs). In this study, 41 papillomas from 30 neotropical parrots were examined by PCR with PsHV-specific primers. All 41 papillo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 23 publications
0
35
0
2
Order By: Relevance
“…These genotypes show distinct biological characteristics and the potential to cause PD [102]. On the other hand, PsHV-1 genotypes 1, 2, and 3, but not 4 have been found in mucosal papillomas [96]. The genotypes detected in PD-affected birds are biased according to bird species and their geographic origins.…”
Section: ]mentioning
confidence: 97%
See 1 more Smart Citation
“…These genotypes show distinct biological characteristics and the potential to cause PD [102]. On the other hand, PsHV-1 genotypes 1, 2, and 3, but not 4 have been found in mucosal papillomas [96]. The genotypes detected in PD-affected birds are biased according to bird species and their geographic origins.…”
Section: ]mentioning
confidence: 97%
“…PsHV-1 has also been suggested to have an etiological role in the development of tumors, as specific PsHV-1 genome sequences have been repeatedly detected in mucosal papillomas from parrots [39,64,96]. Recently, another type of psittacid herpesvirus, PsHV-2, has been identified in three African grey parrots.…”
Section: Psittacine Beak and Feather Disease (Circovirus Infection)mentioning
confidence: 99%
“…8 Some of the parrots latently infected with PsHV-1 genotypes 1, 2, and 3 will subsequently develop PsHV-1 DNA containing papillomas of the mucous membranes of the digestive tract. 11 It is assumed that all parrots latently infected with PsHV-1 shed virus at low levels or shed virus intermittently and are a potential source for infection of naïve parrots and a potential source of Pacheco outbreaks or the spread of mucosal papillomas. 2 Two potential means of preventing PsHV-1 infections include the use of immunization or, alternately, testing for and isolation of infected parrots.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in parrots with mucosal papillomas suggest that potential sites for PsHV-1 latency are the mucosa of the oral cavity and the cloaca and analyzing samples of these tissues might be a way to detect latently infected parrots. 11 This hypothesis was tested in a preliminary study that used a PCR assay to examine combined oral and cloacal swabs from parrots believed to be latently infected with PsHV-1. In that study, a population of parrots was found that were positive on multiple samples over a period of 12 months.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation